Processing Purple Sweet Potato Peel as Alternative Material of Textile and Fashion Products with Circular Economic Principles - Yunita Fitra Andriana; Rizka Ramayanti; Nurul Aisyah Rachmawati (Institut Seni Indonesia Denpasar, 2023)
The textile and fashion industries are the most polluting industry in the world. This is because the industries driven by the fashion trend which is rapidly change. During the production and distribution process, the fashion and textile industries produce waste that can damage the air, water and soil. Moreover, the industries use non-renewable materials, and the life span of their product is short, eventually it will end up on the landfill. The application of circular economic principles on the textile and fashion industry is a step in an effort to reduce the level of environmental pollution. In this study, the principles that applied are, using biomaterial, obtain it from local resources, producing less waste, and after use the material can be naturally decomposed. The method used in this research is a qualitative method with an experimental approach. Data collected through a several exploration stages, processing purple sweet potato peel into composite materials. Processing purple sweet potato peel in this study is to produce an alternative raw material for the industries, so that they can use a more environmentally friendly material. Using biomaterials also can adding value to the textile and fashion products, so it can foster awareness to the consumer, in aim to make a systemic social behavioral change. The output of this study is the design of fashion products made of composite materials from purple sweet potato peel which are carried out using digital simulation sketches. The design was made based on the consideration of the character and potential of the composite material from the results of a series of experimental processes, so that the product sketch made is an accessory product consisting of earrings with a relatively small size.